(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This study was conducted to determine the emotions, perceived stressors, and coping strategies during the Covid-19 pandemic among the front liners in the four municipalities Eastern Samar (Maydolong, Balangkayan, Llorente, and Hernani). There were one hundred fifty-seven (157) respondents composed of PNP, BFP, health workers, barangay officials, LGU employees, rescuers, and emergency response team. Convenience sampling was employed for practical accessibility, geographical proximity, and willingness to participate of identified respondents. The study utilized a four-part questionnaire. Part 1 asked the feelings/emotions of respondents, part 2 solicited the factors causing stress, part 3 implored the factors that help reduce stress, and part 4 elicited the personal coping strategies to alleviate stress. Findings showed that the feelings/emotions of respondents were interpreted as “slightly emotional” which shows that respondents are professionals and ethically responsible which drove them to continue working. The results on the factors causing stress revealed that “lack of cooperation among the residents on following health protocols” with a mean of 3.0 was interpreted as “moderately stressed.” On factors that help reduce stress, it showed that knowing how to be infected and how to prevent the virus from contamination does not really help in reducing stress. This study found out that personal coping strategies to alleviate stress were often used by the respondents.